Giving a Herbal Drink â€œHot Gingerâ€ to Relieve Menstrual Pain to Students at the Islamic Boarding School Kediri - Margareta Andini, Dwi; Rosita Dewi, Ayu (Journal of Advanced Nursing and Health Sciences, 2024)
Menstruation is a natural physiological change that occurs in every woman and is influenced by reproductive hormones, FSH (estrogen) or LH (progesterone). When you are menstruating, usually women will experience pain or cramps in the lower abdomen; this is called dysmenorrhea. One of the treatments for menstrual pain is traditional medicine using ginger ale. To analyze the effectiveness of giving ginger wedang to reduce the intensity of dysmenorrhea pain in female students in islamic boarding schools. This study uses a type of research. quasi-experimental, that is, with a one-group pretest-posttest design. With a population of students at the Islamic boarding school kediri as many as 86 students. The sampling was carried out by purposive sampling, so a sample of 31 respondents was obtained. Meanwhile, data analysis uses the Wilcoxon Signed Rank Test formula. The results showed that the intensity of dysmenorrhea on day 1 before being given ginger tea had most of the respondents on a pain scale of 7-9 with an average pain scale of 6.9, and after being given ginger tea on day 2, the pain intensity scale of most respondents decreased between 1- 3 with an average of 1.9. The results of the Wilcoxon Signed Rank Test obtained a significance value of 0.003. Giving wedang jahe during menstrual pain is believed to reduce the intensity of dysmenorrhea pain